2020
DOI: 10.1088/1361-6528/abcacc
|View full text |Cite
|
Sign up to set email alerts
|

Single-walled carbon nanotube membranes as non-reflective substrates for nanophotonic applications

Abstract: We demonstrate that single-walled carbon nanotube (SWCNT) membranes can be successfully utilized as nanometer-thick substrates for enhanced visualization and facilitated study of individual nanoparticles. As model objects, we transfer optically resonant 200 nm silicon nanoparticles onto pristine and ethanol-densified SWCNT membranes by the femtosecond laser printing method. We image nanoparticles by scanning electron and bright-field optical microscopy, and characterize by linear and Raman scattering spectrosc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…The electronic band structure for the zigzag tubes (10, 0), (12, 0), (14, 0), (15, 0), (16, 0) and (17, 0) (see Fig. 1) and for the armchair tubes (4,4), (6,6), (8,8), (10,10), (14,14) and (16,16) (see Fig. 2) were determined and investigated using TB calculations including π orbitals only in the high symmetry directions in the BZ between the Γ and K points.…”
Section: Geometrical Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…The electronic band structure for the zigzag tubes (10, 0), (12, 0), (14, 0), (15, 0), (16, 0) and (17, 0) (see Fig. 1) and for the armchair tubes (4,4), (6,6), (8,8), (10,10), (14,14) and (16,16) (see Fig. 2) were determined and investigated using TB calculations including π orbitals only in the high symmetry directions in the BZ between the Γ and K points.…”
Section: Geometrical Parametersmentioning
confidence: 99%
“…Since the discovery of SWCNTs in 1993 [2], this novel nanostructured material has attracted enormous attention from the scientific community in several fields due to their extraordinary mechanical, electrical, thermal, vibrational and optical properties [3][4][5][6][7]. This unique combination of properties make this material a suitable candidate for a wide range of various potential applications in areas from integrated circuits [8], photovoltaics [9], nanophotonic applications [10], energy storage [11], interconnects [12,13], spintronic devices [14], sensors [15], batteries [16], transistors [17,18], light detectors [19] and light emitters [20]. This has sparked interest in experimentalists and theoreticians.…”
Section: Introductionmentioning
confidence: 99%
“…This study reported that using SWCNT produced a membrane with better optical contrast than a pristine membrane. The high transparency yield, low reflection rate, and small thickness make SWCNT membranes potential for applications in nanophotonics, bioimaging, and the science of synchrotron radiation [15] .…”
Section: Introductionmentioning
confidence: 99%